Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1523/jneurosci.0155-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Modulates the p53 Response in Neurons Exposed to DNA Damage

Abstract: Previous studies have shown that DNA damage-evoked death of primary cortical neurons occurs in a p53 and cyclin-dependent kinasedependent (CDK) manner. The manner by which these signals modulate death is unclear. Nuclear factor-B (NF-B) is a group of transcription factors that potentially interact with these pathways. Presently, we show that NF-B is activated shortly after induction of DNA damage in a manner independent of the classic IB kinase (IKK) activation pathway, CDKs, ATM, and p53. Acute inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 67 publications
7
85
2
2
Order By: Relevance
“…[92][93][94] It has been reported that NF-kB is rapidly activated following DNA damage in cultured neurons in an IKK-ATM-and p53-independent manner. 95 Data in the latter study suggested that NF-kB acts upstream of p53 in acute cell death induced by DNA damage, but, on the other hand, NF-kB promotes cell survival when activated over a longer time period in the absence of severe DNA damage. However, in another study, DNA-damaging agents reduced NF-kB activity in cultured neurons and treatment with a p53 inhibitor resulted in preservation of NF-kB activity.…”
Section: Chronic Neurodegenerative Disordersmentioning
confidence: 84%
“…[92][93][94] It has been reported that NF-kB is rapidly activated following DNA damage in cultured neurons in an IKK-ATM-and p53-independent manner. 95 Data in the latter study suggested that NF-kB acts upstream of p53 in acute cell death induced by DNA damage, but, on the other hand, NF-kB promotes cell survival when activated over a longer time period in the absence of severe DNA damage. However, in another study, DNA-damaging agents reduced NF-kB activity in cultured neurons and treatment with a p53 inhibitor resulted in preservation of NF-kB activity.…”
Section: Chronic Neurodegenerative Disordersmentioning
confidence: 84%
“…Briefly, neurons from each embryo were plated individually, into six-well dishes (B3 million cells/well) coated with poly-D-lysine (100 mg/ml) in serum-free medium (MEM/F12 (1:1) supplemented with 6 mg/ml D-glucose, 100 mg/ml transferrin, 25 mg/ml insulin, 20 nM progesterone, 60 mM putrescine and 30 nM selenium) as described previously. 38 At 2 days in vitro, cortical neurons were treated with TM (3 mg/ml) for 8 h. Stock solutions of TM were prepared in DMSO (Sigma Aldrich, Oakville, ON, Canada) and diluted in culture media immediately before addition. Total RNA was isolated from cells at indicated time points using TRIzol reagent as per manufacturer's instructions (Invitrogen).…”
Section: Discussionmentioning
confidence: 99%
“…An indirect mechanism through which NF-B is able to regulate Noxa gene transcription was suggested by Aleyasin et al (2004). These authors found that, when DNA had been damaged, NF-B stimulated Noxa and Puma gene transcription through induction of p53 expression.…”
Section: Mandola 2001mentioning
confidence: 99%